Intense pulsed light, a promising technique to develop molybdenum sulfide catalysts for hydrogen evolution. (18th February 2019) - Gupta, Alexander; Ankireddy, Krishnamraju; Kumar, Bijendra; Alruqi, Adel; Jasinski, Jacek; Gupta, Gautam; Druffel, Thad
Abstract: We have demonstrated a simple and scalable fabrication process for defect-rich MoS2 directly from ammonium tetrathiomolybdate precursor using intense pulse light treatment in milliseconds durations. The formation of MoS2 from the precursor film after intense pulsed light exposure was confirmed with XPS, XRD, electron microscopy and Raman spectroscopy. The resulting material exhibited high activity for the hydrogen evolution reaction (HER) in acidic media, requiring merely 200 mV overpotential to reach a current density of 10 mA cm −2 . Additionally, the catalyst remained highly active for HER over extended durability testing with the overpotential increasing by 28 mV following 1000 cycles. The roll-to-roll amenable fabrication of this highly-active material could be adapted for mass production of electrodes comprised of earth-abundant materials for water splitting applications.